2006
DOI: 10.1124/jpet.106.106823
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Improves Diabetes-Induced Coronary Endothelial Dysfunction

Abstract: 3-Hydroxy-3-methylglutaryl CoA reductase inhibitors decrease cardiovascular morbidity in diabetic patients, but the mechanism is unclear. We studied the actions of simvastatin (SIM) in enhancing NO bioavailability and reducing oxidative stress in coronary vessels from diabetic rats and in rat coronary artery endothelial cells (RCAEC) exposed to high glucose. Coronary arteries isolated from diabetic rats showed decreases in acetylcholine (ACh)-mediated maximal relaxation from 81.0 Ϯ 4.5% in controls to 43.5 Ϯ 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
0
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 37 publications
8
37
0
4
Order By: Relevance
“…According to recent reports, statins, including fluvastatin, exert a positive influence on the cardiovascular system not only by regulating blood lipids but also in a cholesterol-independent manner [34,35] . Tawfik et al demonstrated that simvastatin, a drug similar to fluvastatin, prevented impaired coronary endothelial cell-dependent vasorelaxation in 4-week STZ-induced diabetic rats [36] . Moreover, statins up-regulated neuronal nitric oxide synthase (nNOS) expression in the rostral ventrolateral medulla (RVLM), a vasomotor center in the brainstem, down-regulated sympathetic nerve activity and achieved an improvement in the BRS [37] .…”
Section: Discussionmentioning
confidence: 99%
“…According to recent reports, statins, including fluvastatin, exert a positive influence on the cardiovascular system not only by regulating blood lipids but also in a cholesterol-independent manner [34,35] . Tawfik et al demonstrated that simvastatin, a drug similar to fluvastatin, prevented impaired coronary endothelial cell-dependent vasorelaxation in 4-week STZ-induced diabetic rats [36] . Moreover, statins up-regulated neuronal nitric oxide synthase (nNOS) expression in the rostral ventrolateral medulla (RVLM), a vasomotor center in the brainstem, down-regulated sympathetic nerve activity and achieved an improvement in the BRS [37] .…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms might participate in the improvement of endothelial dysfunction observed with statins in different cardiovascular pathologies. 22,39,40 Atorvastatin downregulated the increase in collagen content and improved the alterations of elastin structure induced by Ang II in MRA. More importantly, these effects had a physiological consequence.…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of the two drugs were in parallel, the neuro and vascular protective effects of atorvastatin were usually superior to those of FeTPPs, but did not reach significance, a fact possibly attributable to the pleiotropic effects of statins, including antioxidant effects and inhibition of GTP-binding proteins, in addition to their known cholesterol-lowering ability [13,17,[45][46][47][48]. While previous studies examined the protective effects of statins in retinas from ischaemia/reperfusion models or in other tissue from diabetic animals, our study is the first to demonstrate the neuroprotective effects of atorvastatin in the diabetic retina.…”
Section: Discussionmentioning
confidence: 99%